SEX-RELATED DIFFERENCES IN CARDIOVASCULAR-RESPONSES TO COMMON CAROTID OCCLUSION IN CONSCIOUS RATS - Bedrandecastro, MTB; Bedrandecastro, J. C. (Associação Brasileira de Divulgação Científica (ABRADIC), 1992)
Mean arterial pressure and heart rate were determined in conscious, unrestrained groups of 10 male, female and androgenized female Wistar rats 20 s (early pressor response) and 1 min (late sustained response) after bilateral carotid artery occlusion. The early pressor response, which is of carotid reflex origin, was 40% greater in female than in male rats (45 +/- 2 vs 63 +/- 3 mmHg, respectively). The late sustained response, which is of central origin (probably ischemic), did not differ between male and female rats (32 +/- 2 vs 37 +/- 4 mmHg, respectively). The magnitude of the early pressor response of androgenized female tats (50 +/- 2 mmHg) was similar to that of male rats (45 +/- 2 mmHg) but the late sustained response was 19% smaller (26 +/- 2 mmHg). Common carotid occlusion caused increases in heart rate which were greater in female (51 +/- 9 and 34 +/- 9 beats/min in the early pressor response and late sustained response, respectively) than in male rats (31 +/- 5 and 8 +/- 4 beats/min, respectively). In androgenized female rats, heart rate decreased during common carotid occlusion (34 +/- 7 and 35 +/- 8 beats/min after 20 s and 1 min, respectively). These data provide evidence that there are substantial sex-related differences in the cardiovascular responses to common carotid occlusion in conscious rats and indicate that administration of androgens to newborn female rats affects the baroreceptor reflex control of their arterial pressure.
Keywords: CAROTID ARTERY OCCLUSION; BARORECEPTOR REFLEX; SEXUAL DIMORPHISM; NEONATAL ANDROGENIZATION